2014
DOI: 10.1021/cs500802d
|View full text |Cite
|
Sign up to set email alerts
|

Bioelectrocatalytic Oxidation of Alkanes in a JP-8 Enzymatic Biofuel Cell

Abstract: Alkanes are attractive fuels for fuel cells due to their high energy density, but their use has not transitioned to biofuel cells. This paper discusses the development of a novel enzyme cascade utilizing alkane monooxygenase (AMO) and alcohol oxidase (AOx) to perform mediated bioelectrocatalytic oxidation of hexane and octane. This was then applied for the bioelectrocatalysis of the jet fuel JP-8, which was tested directly in an enzymatic biofuel cell to evaluate performance. The enzymatic catalysts were shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…As a comparison to using the promiscuous AOx enzyme in the PEC, a more substrate-specific enzyme, ADH (alcohol dehydrogenase), was also studied. 33 While ADH is also known to perform alcohol oxidation, it is dependent on the diffusional cofactor NAD + /NADH rather than a bound FAD. 30 In the case of NAD + -dependent ADH, the reaction thermodynamics heavily favor the alcohol, requiring continuous regeneration of NAD + via NADH oxidation for increased BA production.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…As a comparison to using the promiscuous AOx enzyme in the PEC, a more substrate-specific enzyme, ADH (alcohol dehydrogenase), was also studied. 33 While ADH is also known to perform alcohol oxidation, it is dependent on the diffusional cofactor NAD + /NADH rather than a bound FAD. 30 In the case of NAD + -dependent ADH, the reaction thermodynamics heavily favor the alcohol, requiring continuous regeneration of NAD + via NADH oxidation for increased BA production.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The use of FAD-GDH, which is oxygen insensitive (unlike glucose oxidase) and can now be obtained commercially, has only very recently reported in combination with quinone-modified buckypapers, and promisingly, gave high catalytic currents up to 1.97 mAcm - Enzymatic biofuel cells have also been explored as portable, low-temperature and sulfurinsensitive alternatives to solid oxide fuels cells that run on JP-8 jet fuel, for example, for military applications. Minteer and coworkers exploited an enzyme cascade of alkane monooxygenase (AMO) and alcohol oxidase (AOx) at a MWCT buckypaper (Buckeye Composites) anode for mediated bioelectrocatalytic oxidation of hexane, octane, and jet fuel 67 . This study demonstrated the possibility to exploit alkanes as fuels for biofuel cells for the first time, and additionally, showed the possibility to produce power densities up to 3 mW cm -2 without pre-processing of alkane-based fuels.…”
Section: Portable Enzymatic Biofuel Cellsmentioning
confidence: 99%
“…These less traditional techniques include extraction using ionic liquids [34][35][36][37][38] and biodesulfurization using bacteria [39][40][41][42] or enzymes. 43 These techniques, while effective, are not as portable as adsorptive desulfurization, which would be ideal for eld applications.…”
Section: Current Research Directions and Adsorptive Desulfurization Fmentioning
confidence: 99%